Isovist-Based Occlusion Maps Representing Critical Variations in Le Corbusier's Museum of Unlimited Extension. (February 2014) - Christenson, Mike
The application of occlusion maps (ie, two-dimensional isovists deployed in a field) to several iterations of Le Corbusier's Museum of Unlimited Extension are described. Built and unbuilt works are considered. Special focus is given to Le Corbusier's design for the National Museum of Western Art in Tokyo both before and after additions. Comparison and analysis of occlusion maps in the context of floor plans and perspective images are used to highlight critical variations between the projects.